KEEFEKTIFAN KELOMPOK TANI PADI SAWAH DI KECAMATAN SUKOHARJO KABUPATEN PRINGSEWU - Pranata, Doni; Effendi, Irwan; Rangga, Kordiyana K (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
The purpose of this research is to know: the effectiveness of paddy farmer groups; relationship between group dynamics and the effectiveness, and relationship between farmer group effectiveness and paddy productivity level. This research was conducted in Sukoharjo Sub District, Pringsewu Regency with 73 respondents of paddy farmers.  Research method used is a survey method with descriptive analysis and using statistical nonparametric rank Spearman correlation to test hypothesis.  The results showed that paddy farmer groups in Sukoharjo Subdistrict had a high level of effectiveness, group dynamics had significant relationship with farmer group effectiveness, and farmer group effectiveness had significant relationship with paddy productivity level of paddy farmer groups.   Key words: effectiveness, farmer group, group dynamics